Comparative analysis of Hymenasplenium (Aspleniaceae) chloroplast genomes from China - Yanfen Chang; Zhixin Wang; Guocheng Zhang; Na Wang; Limin Cao (PeerJ)
Hymenasplenium is one of the two genera in the large fern family Aspleniaceae. A previous study explored the molecular phylogeny of this genus using several chloroplast DNA fragments and identified three major clades, one of which is the monophyletic Old World clade with southwestern China as its diversity center. To date, there were only a few studies conducted on chloroplast genomes in Hymenasplenium or Aspleniaceae, limiting the understanding of the plastome features and its role in evolution of this group. Here, we studied the complete chloroplast genomes of 12 Hymenasplenium species covering all four subclades of the Old World clade distributed in China. The length of the Hymenasplenium plastomes ranged from 151,617 to 151,930 bp, and contained 129 genes in total, comprising 87 protein-coding, 34 tRNA, and eight rRNA genes. The GC content ranged from 41.8% to 42.1%. Comparative analyses of the Hymenasplenium chloroplast genomes displayed conserved genomic structure and identical gene arrangement. A total of 1,375 simple sequence repeats and 1,639 large repeats were detected. In addition, we detailed hypervariable regions that can be helpful for further phylogenetic research and species delimitation in Hymenasplenium. Furthermore, we supported phylogenetic relationships among major groups as well as possible cryptic speciation found in previous research in the genus. Our study provides new insights into evolutionary history and basic resources for phylogenetic and taxonomic studies of the genus Hymenasplenium.